THE INFLUENCE OF JOB INVOLVEMENT, COMPETENCE AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFOMANCE AT PT DHANA PERSADA - Rysnanda Kurniawan Sunariyo; Sri - Wahyuni; Endang Sulistiyani (JOBS (Jurnal Of Business Studies), 2017)
The aim of this study is to analyze the influence of job involvement, competence, and employee engagement on employee performance at PT Dhana Persada Manunggal Semarang. Research variables include: job involvement (X1), competence (X2), employee engagement (X3), as independent variables, and employee performance (Y) as dependent variable. This study used multiple linear regression analysis. The population in this study were all employees of PT Dhana Persada Manunggal Semarang, amounting to 50 people. Samples are selected using the method of saturated sampling that all members of the population sample used as samples or also called census research. Data collections techniques are using questionnaires, interview, observation, and literature review. Based on the result of this study, job involvement, competence, and employee engagement have positively and significantly influence on employee performance. While the adjusted R square has value 68,3%, it means that job involvement, competence, and employee engagement give contribution to employee performance (Y) on 68,3% while 31,7% influenced by other variables which were not described in this study.